The under-representation of women in coaching: A comparison of male and female Canadian coaches at low and high levels of coaching - Reade, I.; Rodgers, W.; Norman, L. (International Journal of Sports Science and Coaching, 2009)
There are disproportionately few women in high level coaching positions. Explanations vary for this under-representation of women as coaches, but the focus of this research is the disproportionate gender ratio within the profession as based upon Kanter's framework of occupational sex segregation. Two studies examining Canadian coaches undertaking introductory coaching certification (Study 1) (n = 809) and high-performance coaches (Study 2) (n = 819) were conducted. Both studies contribute evidence of decreasing proportions of women coaches from early certification and recreational positions to high-performance positions despite little difference between men and women in terms of qualifications including education and competitive experience. The results are discussed in terms of Kanter's proposition of proportion, along with references to power and opportunity within the coaching profession. Potential administrative practical solutions to the problems are suggested.